Novel graft copolymers with aliphatic polyether and polyester main chains - Zhang, Haiping; Jakisch, Lothar; Komber, Hartmut; Haeussler, Liane; Voit, Brigitte; Boehme, Frank (Polymer, 2015)
A series of new graft copolymers was synthesized by a "grafting to" approach, in the course of which the polymer backbone was build up first by a chain extension reaction of polyether or polycaprolactone diols with bis-N-acyl lactams. During the first reaction step, benzoxazinone groups were introduced into the backbone which served as grafting sites for monoamino-terminated polyamide 12 or polystyrene. Chain extension and grafting could be performed successively and with high selectivity in the melt at 180-220 °C. The morphology and the thermo-mechanical behavior of the graft copolymers were strongly influenced by the type of the grafted side chains. Polymers with polyamide grafts exhibited a two phase morphology with a spherulitic superstructure in the micrometer scale. The tensile behavior of these polymers was characterized by a certain elastic component. In contrast, the phase morphology of a polystyrene grafted polymer was much finer. A strong influence on the glass transitions revealed improved compatibility between the components. Pronounced strain hardening was observed during the tensile test of polystyrene grafted samples.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Aliphatic polyether; Coupling reactions; Graft copolymers